Lu-La's Guide to Space A Shaun the Sheep Movie Farmageddon (Leicester Sweet Cherry Publishing, 2019)
Learn all about space with Shaun the Sheep's friend Lu-La! This guide is packed with interesting facts and colourful images. Great for inspiring young minds! Perfect for children aged six and above
Packed with Space facts, A fun quiz, stickers & A stellar poster
The World Around Us (outer space)
Keywords: Space